Culture dimensions and it capability influence on organizational intelligence of Libyan oil and gas companies / Hadya S. Hawedi - Hawedi, Hadya S. (Institute of Graduate Studies, UiTM, 2015)
Different groups have different culture. In Libya there are different ethnic culture and they are the main managers in the Libyan oil and gas companies. These ethnic groups include four main groups Arab, Berbers (Amazigh), Toubou and Tuaregs and each group has their own language, heritage, customs, values and beliefs even they have their own flag. The role of information technology capability in mediating the influence between cultural dimensions and organizational intelligence which ultimately contributes towards the performance of the companies are competitive advantage. The Libyan oil and gas companies are in dispersed locations, which necessitate an efficient and effective management system to improve their competitiveness, they need to pool resources in the organization to create organizational intelligence as to be competitive. Organizational intelligence is organizational practices which are influenced by cultural dimensions and IT capability. The objective of the study is to investigate how cultural dimensions influences organizational intelligence through IT capability in the Libyan oil and gas companies. These culture dimensions include resonant leadership, ethnic culture and organization culture. A quantitative research method based on survey questionnaire was used to collect numerical data that were statistically analysed using descriptive and inferential statistics based on Statistical Package of Social Science (SPSS) software and AMOS module…